Fuel Efficient Propellers A boon to the Indian fishing industry - Nasser, M.; Lalitha, K. V.; Ashaletha, S.; Geethalekshmi, V. (Indian Farming, 2015)
The pelagic fishery sector of the country alone consume around 200 million litres of fuel per annum. The trend of increasing engine power to achieve more speed to reach the fishing ground faster aggravates the issue of wastage of fuel and leads to great loss to fishers and environmental problems like increased carbon emission. Due to unscientific design propellers, this loss increases and also causes huge expenditure on maintenance / frequent replacement of propellers. The improved blade element design of propellers proved fuel saving in ring seiners by 18-21%. This intervention can benefit the sector consisting of about 1100 vessels and could save around 14-19 million litres of diesel per annum worth around 63-78 crore rupees. It will also help to reduce 51,000 tonnes of CO2 emission per annum. The techniques developed for this sector can be customized for creating appropriate designs for other sectors like trawlers to achieve still higher fuel saving.